Prediction and Diagnosis of Typhoon Morakot (2009) Using the Naval Research Laboratory's Mesoscale Tropical Cyclone Model - Eric A. Hendricks (Terrestrial, Atmospheric and Oceanic Sciences, 2011)

(untitled)
Numerical simulations of Typhoon Morakot (2009) were performed using the Naval Research Laboratory¡¦s Coupled Ocean/Atmosphere Mesoscale Prediction System for Tropical Cyclones (COAMPS-TC). COAMPS-TC was run in real-time in 2009 in the western North Pacific Ocean basin, and simulations of Morakot were executed during its life cycle, from formation through landfall in Taiwan. In this work, an evaluation of the model¡¦s performance is presented. The COAMPS-TC average track errors were small and very close to those of the consensus. Further, the intensity errors were small; the mean absolute intensity error at the 48 h lead time was 9 kt. Particular focus was placed on the 72-h simulation beginning on 1200 UTC 6 August, encompassing the time frame before, during and after landfall. COAMPS-TC was able to predict the structure of Morakot reasonably well before and after landfall, capturing a large asymmetric tropical cyclone with the precipitation shield shifted to the south of its center. Qualitatively, the precipitation forecast was consistent with observations from the Taiwan rain gauge network, as the model was able to predict two maxima, in both the northern and southern portions of the central mountain range. However, the accumulated precipitation maximum in the southern portion of the central mountain range was underpredicted by approximately 50%. The underprediction in precipitation by COAMPS-TC in southern Taiwan was due to four factors: (i) the premature dissipation of tropical storm Goni causing errors in the large-scale flow and moisture pattern after landfall, (ii) inaccuracies in the spatial location and timing of convective and stratiform precipitation as Morakot interacted with land and the southwest monsoon flow, (iii) a simulated track that moved slightly too slow prior to landfall and slightly too fast after landfall, and (iv) a horizontal resolution (5-km) that may be too coarse to resolve the interaction of convection with the complex topography.